Weather based forewarning of root mealy bug, Paraputo sp. (Pseudococcidae : Hemiptera) in mulberry of Kalimpong hills (The Journal of Plant Protection Sciences, 2021)
Kalimpong hills in Darjeeling district endowed forewarning or prediction system by  with sub-tropical climate, is congenial for monitoring or predicting the pest population  rearing of bivoltine silkworm superior in (10). It is being widely used in the agricultural  quality in comparison to hybrids reared in production system now-a-days as a tool for  plains of West Bengal. Bivoltine silkworms can lesser damage to natural enemy complex and  be successfully reared during March-October also limits environmental pollution by way of  when adequate rainfall and prevailing reduced pesticide application on requirement  temperature facilitates production of adequate basis and apply when necessary strategy. The  mulberry foliage.
Keywords: Darjeeling; monitoring; Kalimpong